2017
DOI: 10.1001/jamaoncol.2017.0013
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Multi-institutional, Pathologist-Based Assessment of 4 Immunohistochemistry Assays for PD-L1 Expression in Non–Small Cell Lung Cancer

Abstract: Importance Four assays have been registered with the FDA to detect PD-L1 to enrich for patient response to anti-PD-1/PD-L1 therapies. The tests use four separate PD-L1 antibodies on two separate staining platforms and have their own scoring systems which raises questions about their similarity and potential cross-utilization. Objective We compared the performance of four PD-L1 platforms, including two FDA-cleared assays and two laboratory developed tests (LDTs). Design Four serial histology sections from 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
490
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 675 publications
(550 citation statements)
references
References 19 publications
37
490
4
1
Order By: Relevance
“…Third, it only compares the performance of four PD-L1 platforms; there are no therapeutic outcome data to evaluate the clinical predictive power of alternative PD-L1 IHC testing strategies. Recent United States-based study concurs with the Blueprint study (12). This study was funded by pharmaceutical companies (Bristol-Myers Squibb) and the NCCN oncology research programme.…”
supporting
confidence: 55%
“…Third, it only compares the performance of four PD-L1 platforms; there are no therapeutic outcome data to evaluate the clinical predictive power of alternative PD-L1 IHC testing strategies. Recent United States-based study concurs with the Blueprint study (12). This study was funded by pharmaceutical companies (Bristol-Myers Squibb) and the NCCN oncology research programme.…”
supporting
confidence: 55%
“…The latter finding is supported by another study that suggested that SP142 might have higher specificity, but lower sensitivity, when compared with 22C3 and that it typically underestimated PD-L1 scores for treatment with pembrolizumab 20 . A prospectively designed, statistically powered trial assessed 4 assays, including 22C3, E1L3N, 28-8, and SP142, and found the SP142 assay to be an outlier, detecting significantly less PD-L1 expression in tumour cells; however, excellent concordance and reproducibility between the other 3 assays was demonstrated, with the authors concluding that they were equivalent 21 . Although excellent concordance was seen when samples were obtained from tumour cells, greater variability was observed when scoring immune cells with any antibody 20,21 .…”
Section: Phase III Trials In Previously Treated Patientsmentioning
confidence: 99%
“…Variability in PD-L1 testing can arise because of the type (tumor cells, immune cells, or a combination) and percentage cutoffs used for positivity, archival versus fresh tissue, primary versus metastatic biopsies, diversity of antibodies utilized, and tumor heterogeneity [86,87]. Several comparative studies across different PD-L1 assays have been conducted, including collaborative studies between industry and academic institutions [88][89][90][91]. The outcomes of these studies have varied, with two studies showing concordance among assays [88,90], one study showing equivalence for most assays [91], and one study revealing differences across all of the assays that do not support interchangeability [89].…”
Section: Immunotherapeutics and Patient Selectionmentioning
confidence: 99%
“…Several comparative studies across different PD-L1 assays have been conducted, including collaborative studies between industry and academic institutions [88][89][90][91]. The outcomes of these studies have varied, with two studies showing concordance among assays [88,90], one study showing equivalence for most assays [91], and one study revealing differences across all of the assays that do not support interchangeability [89]. Based on these preliminary findings, the PD-L1 assays that are currently available are not considered interchangeable.…”
Section: Immunotherapeutics and Patient Selectionmentioning
confidence: 99%